Improving quality and machining efficiency of hole during AlN trepanning with nanosecond pulse laser. Issue 15 (15th October 2020) - Wang, Lingzhi; Zhao, Wanqin; Mei, Xuesong; Yang, Zixuan; Shen, Xiaowei; Liu, Haodong
Abstract: Aluminum nitride (AlN) is essential material to electronics industry. Compared to traditional machining methods, laser trepanning has become one of the most popular options for hole machining on AlN. Due to involvement of multiple parameters, such as scanning number, laser beam jump direction, scanning mode, and filling circle interval, the optimization of hole quality is complex. To tackle this problem, this paper systematically studied hole trepanning on AlN using nanosecond pulse laser in order to examine the relationship among trepanning parameters and hole dimensions, quality, and machining efficiency. Thereby, the optimized combination of parameters could be obtained to improve the quality and efficiency of hole machining. Moreover, possible effect mechanisms like effect of laser fluence on hole diameters, effects of jump directions and scanning modes on hole machining quality were discussed. Most importantly, it is the first time that the relationship among trepanning parameters, hole quality, and machining efficiency is presented.